Care Disruptions and End-Of-Life Care Experiences Among Home-Based Primary Care Patients During the COVID-19 Pandemic in New York City: A Retrospective Chart Review. (February 2023) - Franzosa, Emily; Kim, Patricia; Reckrey, Jennifer M.; Zhang, Meng; Xu, Emily; Aldridge, Melissa D.; Federman, Alex D.; Ornstein, Katherine A.
Background: Research on deaths during COVID-19 has largely focused on hospitals and nursing homes. Less is known about medically complex patients receiving care in the community. We examined care disruptions and end-of-life experiences of homebound patients receiving home-based primary care (HBPC) in New York City during the initial 2020 COVID-19 surge.Methods: We conducted a retrospective chart review of patients enrolled in Mount Sinai Visiting Doctors who died between March 1-June 30, 2020. We collected patient sociodemographic and clinical data and analyzed care disruptions and end-of-life experiences using clinical notes, informed by thematic and narrative analysis.Results: Among 1300 homebound patients, 112 (9%) died during the study period. Patients who died were more likely to be older, non-Hispanic white, and have dementia than those who survived. Thirty percent of decedents had confirmed or probable COVID-19. Fifty-eight (52%) were referred to hospice and 50 enrolled. Seventy-three percent died at home. We identified multiple intersecting disruptions in family caregiving, paid caregiving, medical supplies and services, and hospice care, as well as hospital avoidance, complicating EOL experiences. The HBPC team responded by providing clinical, logistical and emotional support to patients and families.Conclusion: Despite substantial care disruptions, the majority of patients in our study died at home with support from their HBPC team as the practice worked to manage care disruptions. Our findings suggest HBPC's multi-disciplinary, team-based model may be uniquely suited to meet the needs of the most medically and socially vulnerable older adults at end of life during public health emergencies.